A molecular dynamics study to investigate the local atomic arrangements during martensitic phase transformations - Celik, F. A.; Yildiz, A. K.; Ozgen, S. (Taylor & Francis Ltd, 2011)
In this study, the local atomic rearrangements caused by thermally induced martensitic phase transitions in Ni-37.5 at.% Al alloy model based on embedded atom method are studied using molecular dynamics simulations. The local atomic orders and defective structural part of the transformed regions are analysed using the bond orientational order parameters, which are employed mainly to diagnose short-range order of liquid state structures, and the radial distribution functions. In addition, short-range order properties in the model alloy were analysed using Honeycutt-Andersen method, which is commonly used to determine the relationship between atomic pairs. The results of our simulations disclosed that the local atomic rearrangement is of great importance to understand the local character of the transformation path from austenite to martensite phase.
Keywords: alloys; local atomic orders; martensitic phase transitions